Thermophilic microbial agents promote the fermentation progression of spent mushroom compost and pig manure - Du, Hongbo; Lu, Chongchong; Latif, Muhanmad Zunair; Du, Jianfeng; Liu, Yong; Li, Hongxin; Ding, Xinhua (Frontiers in Microbiology, 2025)
Livestock and poultry manure, as a significant organic resource, had an enormous annual production but a utilization rate of less than 50%. Improperly managed manure had become the primary source of agricultural non-point pollution, posing severe challenges to the ecological environment. Achieving efficient resource utilization of livestock manure was a critical step in promoting green agricultural development. Existing research indicated that microbial activity significantly influences the transfer and dissemination of antibiotic resistance genes (ARGs) and the community dynamics of human pathogenic bacteria (HPB) during pig manure composting. However, the specific mechanisms remain unclear. This study innovatively introduced two thermophilic microbial agents (TMS1 and CTMS2) into a pig manure-spent mushroom compost (SMC) aerobic composting system to systematically investigate their regulatory effects on pollutant reduction. The results showed that persistent ARGs (ErmF, ErmQ, ErmX, blaR1, QnrA1, QnrA6, bla-F, QnrA2, QnrA5, Qnra4 and bla-VIM) primarily rely on vertical gene transfer (VGT) for dissemination, whereas easily removable ARGs (tetX, tetW, tetG, tetC, suI1 and suI2) were regulated by both horizontal gene transfer (HGT) and VGT. Notably, the co-addition of thermophilic microbial agents and SMC reduced persistent ARGs by lg0.45–3.73, significantly decreased the abundances of HPB such as Bacteroides and Treponema, and reduced the enrichment of related metabolic pathways, greatly improving compost quality. In stark contrast, the control group (with only SMC and no thermophilic microbial agents) exhibited ARG proliferation. Overall, the application of thermophilic microbial agents not only extended the high temperature phase of composting by over 30% and shortened the composting cycle by 50%, but more importantly, it achieved comprehensive improvement in compost quality by selectively enriching functional microbial communities such as Pseudomonas. This study provides a theoretical foundation and data support for the industrial application of CTMS2 in the safe production of organic fertilizers and the synergistic control of environmental risks.